2019
DOI: 10.3390/ijerph16152807
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Reverse vs. Traditional Linear Training Periodization in Triathlon

Abstract: The present research aimed to analyze the modification in performance, body composition, and autonomic modulation of reverse and traditional linear training periodization in amateur triathletes. We analyzed running and swimming performance, strength manifestation, body composition, and autonomic modulation before and after a traditional linear training periodization (four weeks of volume-based training plus four weeks of intensity-based training plus two-week tapering), a reverse linear training periodization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…The increases in VO 2 max and the speed at VO 2 max obtained by reverse and BP highlighted the effectiveness of both systems to reach aerobic physiological markers, but reverse periodization was more efficient since a lower training volume was performed. The increases in VO 2 max and speed at VO 2 max were in consonance with previous authors in equaled volume training periodization in cycling, triathlon, and swimming [12,13,23], showing how these methods also improve aerobic performance in running. In the same way, the decreased in HR at VT2 was in line with other research conducted with swimmers [6]; nevertheless, in this study, improvement in swimming speed was found, in contrast to the present research, where most likely the different performance level and sport modality could explain this difference.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The increases in VO 2 max and the speed at VO 2 max obtained by reverse and BP highlighted the effectiveness of both systems to reach aerobic physiological markers, but reverse periodization was more efficient since a lower training volume was performed. The increases in VO 2 max and speed at VO 2 max were in consonance with previous authors in equaled volume training periodization in cycling, triathlon, and swimming [12,13,23], showing how these methods also improve aerobic performance in running. In the same way, the decreased in HR at VT2 was in line with other research conducted with swimmers [6]; nevertheless, in this study, improvement in swimming speed was found, in contrast to the present research, where most likely the different performance level and sport modality could explain this difference.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding jump performance results, a previous study reported an interference effect of aerobic endurance exercise on strength and power gains [12]. In addition, a recent study showed that traditional periodization negatively affected jump performance in endurance athletes, but reverse periodization improved it [13]. In this way, our results showed that variations in training periodization could interfere with lower body power in both groups, suggesting that both RP and BP positively improved CMJ height.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Training is a long-term process where the acquisition of new technical, physiological and psychological skills depends on the psychophysiological status of the athlete. The periodisation of these physiological and psychological skills in the training load, as well as a correct dosage of technical skill training, would allow the coach to assist in the best progression of the athletes [29,30]. In this line, it is important to highlight the need of a climate of trust and personal security to enhance desire and freedom to learn and communicate without fear of failure.…”
Section: Discussionmentioning
confidence: 99%